EFEKTIVITAS PENELUSURAN KTMDU DALAM UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK - Rifqi Najmuddin Hilmi (Jurnal Bisnis, Ekonomi, dan Sains, 2024)
Paying taxes is a citizen's obligation that is carried out by every individual who is forced. If citizens do not pay taxes, the country's infrastructure development will be hampered. In Sumedang Regency itself, there are still many motorised vehicles that do not conduct annual re-registration (KTMDU) by their owners even though vehicle tax is one of the sources of regional income that must be taken into account. This study aims to analyse and describe how the effectiveness of KTMDU tracing, analyse the factors that hinder the effectiveness of KTMDU tracing, and find out efforts to overcome the inhibiting factors of the effectiveness of KTMDU tracing in increasing taxpayer compliance. The research method used is descriptive research with a qualitative approach. The research data analysis technique is by collecting data that has been obtained by researchers from interviews, manuscripts, observation, and documentation. The effectiveness of KTMDU tracing in an effort to improve taxpayer compliance in the Sumedang Region can be said to be quite good, although in its implementation it is still not fully optimal. With the existence of inhibiting factors in the effectiveness of KTMDU tracing, the implementation of KTMDU tracing plans to make efforts to minimise inhibiting factors such as continuing communication, information and education.